Analysis of Discontinuous Space Vector PWM Techniques for a Seven-Phase Voltage Source Inverter - Mohd. Arif Khan; Atif iqbal; Sk Moin Ahmad; zakir husain (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper presents discontinuous space vector PWM (DPWM) techniques for a seven-phase voltage source inverter (VSI). Space vector model of a seven-phase VSI shows that there exist 128 space vectors with different lengths and maps into fourteen sided polygons. A number of possibilities could arise to implement modulation of inverter legs due to large number of available space voltage vectors. Two strategies are adopted here; one utilising large and two middle sets of space vectors to implement discontinuous space vector PWM. Clamping of legs of inverter to either positive or negative dc bus leads to discontinuity in the switching and consequently offers reduced switching loss modulation strategy. A significant reduction in switching losses can be achieved while employing DPWM in a seven-phase VSI. A generalised method is also proposed to realize the DPWM in a seven-phase VSI. Comparison of continuous and discontinuous PWM is presented in terms of switching current ripple. The experimental set-up is illustrated and the experimental results are presented.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.244